Molecular Markers for Thyroid Cancer Diagnosis: Insights from MAPK Pathway Gene Expression Analysis - Breno Pupin; Ramon Varella Diniz; Maricilia Silva Costa; Maurilio Jose Chagas; André Bandiera de Oliveira Santos; Renata de Azevedo Canevari (Biomedicines, 2025)
Background and Objectives: Thyroid cancer is the prevailing endocrine malignancy, with incidence growing over the last decades in the world. The current diagnostic techniques often yield inconclusive results, emphasizing the need for more effective diagnostic approaches. Molecular profiling emerges as a promising avenue for carcinoma differentiation, offering precise insights to guide patient selection for surgical intervention. This study aimed to identify molecular markers in thyroid cancer through the expression analysis of genes within the MAPK pathway, aiming to enhance the sensitivity and specificity of carcinoma diagnosis. Methods: Through a comparative analysis of malignant and benign thyroid samples, we identified 46 genes of the MAPK pathway that exhibited differential expression by PCR array analysis. Results: Validation through RT-qPCR and in silico analysis using TCGA confirmed significant results for CCNA1, CDKN1C, CREB1, FOS, HSPA5, JUN, MAP2K6, and SFN genes identified in our cohort, reinforcing the relevance of these biomarkers. Specifically, noteworthy are our findings regarding the potential diagnostic value of CCNA1 and SFN genes in papillary thyroid carcinoma, while the reduced expression of CDKN1C, FOS, and JUN genes in follicular carcinoma suggests their value in distinguishing the thyroid pathologies. Conclusions: This study identifies promising diagnostic markers, namely CCNA1, CDKN1C, FOS, JUN, and SFN genes, which have the potential to enhance clinical decision-making in thyroid cancer.